Antioxidant and anti-ulcer effects of ethyl acetate fraction of Merremia tridentata (L.) Hallier f. root - Sowndhararajan, Kandhasamy; Chin, Nyuk Ling (Elsevier, 2014)
The present study was aimed to determine the antioxidant and anti-ulcer effects of Merremia tridentata root (Arrow-leaf Morning Glory). Antioxidant potential of crude acetone extract and its fractions was evaluated by using various in vitro assays. In the anti-ulcer study, pre-treatment with ethyl acetate fraction (MEF) (50, 100 and 200 mg/kg b.wt.) significantly protected the ethanol-induced gastric ulcer in rats. Simultaneously, the antioxidant enzyme levels of superoxide dismutase, catalase and glutathione in the stomach tissues were significantly increased while pre-treated with MEF. From the results, MEF has the therapeutical potential to prevent gastric ulceration induced by ethanol.